2008
DOI: 10.1074/jbc.m708523200
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Cytochrome c Oxidase Deficiency in G93A SOD1 Mice Overexpressing CCS Protein

Abstract: G93A SOD1 transgenic mice overexpressing CCS protein develop an accelerated disease course that is associated with enhanced mitochondrial pathology and increased mitochondrial localization of mutant SOD1. Because these results suggest an effect of mutant SOD1 on mitochondrial function, we assessed the enzymatic activities of mitochondrial respiratory chain complexes in the spinal cords of CCS/G93A SOD1 and control mice. CCS/G93A SOD1 mouse spinal cord demonstrates a 55% loss of complex IV (cytochrome c oxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 58 publications
4
36
0
1
Order By: Relevance
“…Changes in the activity of the different complexes of the electron transport chain have been described in tissues obtained from ALS patients, and in cell and animal disease models. Although some of these studies have produced mixed and somewhat contradictory results, the most consistent abnormality in mitochondrial respiratory function has been associated with reduced complex I and IV activity (Browne et al 1998;Kirkinezos et al 2005;Mattiazzi et al 2002;Menzies et al 2002;Rizzardini et al 2006;Son et al 2008). In motor neurons of mutant SOD1 G93A mice a reduction in activity of complex I was observed before disease onset and progressing to inhibition of complex IV at later stages (Jung et al 2002).…”
Section: Mitochondrial Morphological Abnormalities and Dysfunctions Imentioning
confidence: 96%
“…Changes in the activity of the different complexes of the electron transport chain have been described in tissues obtained from ALS patients, and in cell and animal disease models. Although some of these studies have produced mixed and somewhat contradictory results, the most consistent abnormality in mitochondrial respiratory function has been associated with reduced complex I and IV activity (Browne et al 1998;Kirkinezos et al 2005;Mattiazzi et al 2002;Menzies et al 2002;Rizzardini et al 2006;Son et al 2008). In motor neurons of mutant SOD1 G93A mice a reduction in activity of complex I was observed before disease onset and progressing to inhibition of complex IV at later stages (Jung et al 2002).…”
Section: Mitochondrial Morphological Abnormalities and Dysfunctions Imentioning
confidence: 96%
“…Indeed, it has been shown that the mitochondrial pool of ALS-SOD1 mutants causes damage to mitochondrial function and structure [226], and the mitochondrial uptake of ALS-SOD1 mutants is increased upon CCS overexpression [227]. This uptake of ALS-SOD1 mutants results in mitochondrial respiratory defects [228] and an acceleration in SOD1-linked motor neuron disease [227,229].…”
Section: Protein-mediated Copper Insertion Into Ccomentioning
confidence: 99%
“…Although evidence has been provided showing that the removal of such aggregates by the elimination of reactive cysteines from mutSOD1s is able to rescue the viability of transfected cells (5,23), transgenic mice that overexpress both the G93A mutSOD1 and its copper chaperone (CCS) die from an ALS-like disease at a time when cytosolic aggregates are not present, thus questioning about a causal role of such aggregates in the pathogenesis of the disease (28). Interestingly, these mice have a clearly enhanced mitochondrial damage (28,29), and mitochondrial abnormalities appear to be shared by models and patients suffering from ALS (reviewed in Ref. 17).…”
Section: Introductionmentioning
confidence: 99%